Degradation of tetracycline wastewater by suspended biochar as carriers in moving bed biofilm reactor. (3rd September 2022) - Liu, Shaoqi; Chen, Hanyu; Zhang, Xueqi; Zhang, Baozhong; Zhu, Huina; Chen, Hongxia; Wen, Bo; Chen, Lefei
Abstract: To improve the removal efficiency of antibiotics in moving bed biofilm reactor, suspended biochar block was prepared by the one-pot process and was used as carriers to construct a reaction device to study the treatment effect of antibiotic wastewater. The characteristics of the hanging biofilm in wastewater were investigated. And the mechanism of biochar as a biological carrier has been studied. The results showed that in the 45-day experiment, the maximum number of biofilms for suspended biochar carriers was twice 3.4 times that of the high-density polyethylene carriers. When 10 mg/L tetracycline was added to the reactor, the removal efficiency of the tetracycline removal rate was 71.85% and the chemical oxygen demand (COD), total nitrogen (TN), and NH4 + -N removal efficiency reached to 89.95, 61.91 and 85.47% respectively. Suspension biochar carriers can reduce fluctuations in redox potentials, thereby improving the cellular efficiency of microorganisms. Meanwhile, it inhibits the production of soluble microbial products and extracellular polymers, reduces toxic effects, and enhances the adhesion between microorganisms and carriers. The microbial communities of the two carriers were investigated by high-throughput sequencing techniques. Suspended biochar significantly increased the relative abundance of Hydrogenophaga and Comamonas, and improved the ability of nitrification and denitrification. Comamonas could be responsible for tetracycline degradation. HIGHLIGHTS Suspended biochar block was prepared by a one-pot process using peanut shells, floating beads and waste electrode graphite as raw materials. The removal efficiency of the tetracycline and the biological characteristics of biofilms were investigated. The adsorption and aggregation of microorganism action were investigated using the biochar as carriers in a moving bed biofilm reactor tank. Graphical Abstract